Phonological awareness emergence in preschool children with autism spectrum disorder. (January 2019) - Dynia, Jaclyn M; Bean, Allison; Justice, Laura M; Kaderavek, Joan N
Background and aims: Phonological awareness begins to develop during the preschool years and is a primary factor underlying later reading abilities. Previous research has found mixed results on the phonological awareness skills of children with autism spectrum disorders. Therefore, the purpose of the present study is to add to our understanding of phonological awareness in children with autism spectrum disorder by investigating residualized gains in phonological awareness skills over an academic year. Methods: A total of 125 preschool (4- to 5-years old) children including 27 children with autism spectrum disorder, 28 children with language impairment, and 70 typically developing children were the focus of the present study. Participants in the current study represent a subset of participants from a larger study titled, Sit Together and Read. Children completed direct assessments in the beginning (fall) and end of school year (spring) on phonological awareness using the Test of Preschool Early Literacy. Results: A one-way ANOVA compared the phonological awareness skills tasks (syllable/onset-rime, blending/elision, receptive/expressive) in the fall and the spring for each of the three groups (children with autism spectrum disorder, children with language impairment, children who are typically developing). In the fall and the spring, all of the analyses were found to be statistically significant. A Tukey HSD further indicated that children with autism spectrum disorder had significantly lower scores on all of the tasks at both time points compared to the typically developing peers. Children with autism spectrum disorder seem to make gains in phonological awareness tasks similarly to their typically developing peers for most of the phonological awareness tasks. Results from the final regression models indicated that children with autism spectrum disorder made gains similar to those of their typically developing peers for most phonological awareness tasks and that language skills predicted residualized gain for syllable, elision, and receptive tasks, as well as the total score when controlling for condition, IQ, and group status. Social skills were not a significant predictor for any of the tasks. Conclusions: Three main findings emerged: (a) phonological awareness skills seem to be a deficit for children with autism spectrum disorder, (b) in general, autism status does not predict residualized gain in phonological awareness skills, and (c) oral language is a significant predictor of residualized gain in phonological awareness skills. Implication: Early childhood educators should focus on providing high-quality instruction on phonological awareness for children with autism spectrum disorder and researchers should focus on investigating the effectiveness of phonological awareness interventions for children with autism spectrum disorder.